(untitled) (Fiep Bulletin - online, 2013)
The practice of regular physical activity is scientifically recognized by its several benefits, mainly in its preventive character. Even so, it has not been effective in the process of engagement and practice of physical activity in programs designed for elderly. Thus, the goal of this research is to analyze and discuss through a literature review, the aspects of engagement and withdraw of the elderly regarding the physical activity programs and in addition, to present a possibility of joining and attachment to the physical activity programs through the ideals of Health Promotion. Several reasons that influenced in the engagement and abandonment of the physical activity programs by the elderly were verified, such as personal, political, financial, cultural and others. However, it is believed that in a perspective of Health Promotion, in which the elderly can participate effectively in the process of choice, relating the practices with their wishes and needs is crucial for the engagement and attachment in physical activity programs.